Evolution of Brazilian Cities Participating in the Emerging and Sustainable Cities Initiative (ESCI) through the Connected Smart Cities (CSC) Ranking - Almeida, Ana Luísa Rodrigues de; Souza, Josélia Paes Ribeiro de; Oliveira, Lucimara Albieri de; Rodovalho, Sarah Afonso (Scientific Journal ANAP, 2025)
Objective – To analyze the evolution of five Brazilian capitals participating in the Emerging and Sustainable Cities Initiative (ICES) by the Inter-American Development Bank (IDB), based on their performance in the Connected Smart Cities (CSC) Ranking between 2015 and 2024.Methodology – A mixed approach, including document analysis, literature review, and quantitative evaluation of CSC ranking indicators, allowing for a comparative analysis of the urban development of the selected cities.Originality/Relevance – The study addresses a gap by investigating the relationship between international urban sustainability initiatives and the performance of cities in national smart city rankings, offering a critical perspective on the continuity and effectiveness of these policies in the Brazilian context.Results – Florianópolis stood out as the top-performing city overall, excelling in technology, innovation, and quality of life. Vitória performed notably in the health sector, while Palmas showed fluctuations in the ranking, reflecting challenges in the continuity of sustainable urban policies. The study observed that ICES participation brought positive developments, but its long-term impact depends on effective governance and consistent public policies.Theoretical/Methodological Contributions – This work proposes an integrative approach that connects international sustainability policies, smart city rankings, and urban indicator analysis, contributing to the debate on urban performance evaluation methodologies.Social and Environmental Contributions – The research highlights the importance of continuous monitoring and implementation of sustainable public policies to ensure improvements in urban quality of life, fostering more resilient, inclusive, and environmentally responsible cities.
Keywords: Smart cities; Urban sustainability; Public policies